Effect of musical recreation exercises on cholesterol and triglyceride levels in obese women (2-1-3) aged 35-45 years (according to body mass index) - Abbas, Prof. Dr. Qasim Muhammad; Dayem, Prof. Dr. Qais Saeed (Sulaimani Journal for Humanities, 2026)
Using exercises accompanied by music is one of the most important ways to help a person understand and master the rhythm of movement. It is also noteworthy that rhythm is linked to physical and motor abilities, as these components are essential for performing any skill based on a series of successive or sequential movements. Cholesterol is a white, waxy substance that our bodies need to build cells. It is found in the cell membranes of the brain, nerves, muscles, skin, liver, intestines, and heart. It is used to produce many hormones, as well as bile acids that help digest fats. The body needs small amounts of cholesterol to cover these uses, because an increase in it in the blood leads to atherosclerosis. Triglycerides are a type of fat used to store energy and provide energy to muscles. They are found only in small amounts in the blood. High triglyceride levels, along with high LDL cholesterol, may increase the risk of developing diseases. The research problem lies in the following question: Does recreational exercise accompanied by music, according to body mass index, affect cholesterol and triglyceride levels in obese women? (1-2-3) for ages (35-45) years)? The researchers used the experimental method with a pre- and post-measurement design for one experimental group divided according to the degree of obesity (1-2-3) in order to suit the objectives and hypotheses of this study. The research population was determined to be women in Al-Diwaniyah Governorate aged (35-45) years who exercise in private fitness centers. The sample was chosen in a purposive manner, consisting of (45) female participants, and was classified according to the degrees of obesity (1-2-3), with each degree of obesity consisting of (15) participants.
Keywords: Recreational exercises accompanied by music; according to the body mass index; cholesterol triglycerides